DESIGN AND SIMULATION OF DIFFERENT SHAPES MICROSTRIP ANTENNAS FOR S- BAND APPLICATIONS (International Journal of Engineering Sciences & Management Research, 2017)
This paper has the design of different geometry shapes the U slot , H slot, T slot , E, I ,L and F slot developed from a rectangular patch of microstrip antenna . Rectangular patch of width (W)=39 mm, length (L)= 29mm is used . All different shapes proposed antenna has been analysed , designed and simulated using CST ( Computer Simulation Technology ) Microwave studio 2016 and the result are compared with the conventional Rectangular patch antenna . All designed antennas operate in the S band frequency range , which incorporates satellite and military applications . The properties of the antenna such as Return Loss , bandwidth , VSWR , Gain , Directivity , Radiation pattern , Bandwidth % , have been investigated. The substrate material used for the proposed antennas is FR-4 lossy, with the dielectric constant of 4.1..